Spatiotemporal expression and molecular characterization of miR-344b and miR-344c in the developing mouse brain - Leong, Jia Wen; Abdullah, Syahril; Ling, King Hwa; Cheah, Pike See (Hindawi Publishing Corporation, 2016)
MicroRNAs (miRNAs) are small noncoding RNA known to regulate brain development. The expression of two novel miRNAs, namely, miR-344b and miR-344c, was characterized during mouse brain developmental stages in this study. In situ hybridization analysis showed that miR-344b and miR-344c were expressed in the germinal layer during embryonic brain developmental stages. In contrast, miR-344b was not detectable in the adult brain while miR-344c was expressed exclusively in the adult olfactory bulb and cerebellar granular layer. Stem-loop RT-qPCR analysis of whole brain RNAs showed that expression of the miR-344b and miR-344c was increased as brain developed throughout the embryonic stage and maintained at adulthood. Further investigation showed that these miRNAs were expressed in adult organs, where miR-344b and miR-344c were highly expressed in pancreas and brain, respectively. Bioinformatics analysis suggested miR-344b and miR-344c targeted Olig2 and Otx2 mRNAs, respectively. However, luciferase experiments demonstrated that these miRNAs did not target Olig2 and Otx2 mRNAs. Further investigation on the locality of miR-344b and miR-344c showed that both miRNAs were localized in nuclei of immature neurons. In conclusion, miR-344b and miR-344c were expressed spatiotemporally during mouse brain developmental stages.